2006
DOI: 10.1074/jbc.m600257200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and Mg2+ Binding Properties of GCAP-1

Abstract: Guanylyl cyclase-activating protein 1 (GCAP-1) is an EF-hand protein that activates retinal guanylyl cyclase (RetGC) in photoreceptors at low free Ca 2؉ in the light and inhibits it in the dark when Ca 2؉ concentrations rise. We present the first direct evidence that Mg 2؉ -bound form of GCAP-1, not its cation-free form, is the true activator of RetGC-1 under physiological conditions. Of four EF-hand structures in GCAP- In this study, we continue to develop a concept for the processes through which Ca 2ϩ senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
108
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 49 publications
(64 reference statements)
7
108
3
Order By: Relevance
“…Free myristic acid was added from a concentrated ethanol solution to the suspension of bacterial cells to a final concentration of 100 g/ml 20 min prior to the induction with 0.5 mM isopropyl ␤-D-thiogalactopyranoside. Three hours after the induction, the bacterial pellet was harvested and the recombinant GCAPs were purified as described previously in detail (22). The concentration of GCAP-1 and its mutants was determined in 20 mM Na-phosphate buffer (pH 6.5) containing 6 M guanidine hydrochloride using extinction coefficients at 280 nm computed for the individual mutants from their amino acid composition (31) utilizing the ExPASY proteomic WWW server software from the Swiss Institute of Bioinformatics (32).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Free myristic acid was added from a concentrated ethanol solution to the suspension of bacterial cells to a final concentration of 100 g/ml 20 min prior to the induction with 0.5 mM isopropyl ␤-D-thiogalactopyranoside. Three hours after the induction, the bacterial pellet was harvested and the recombinant GCAPs were purified as described previously in detail (22). The concentration of GCAP-1 and its mutants was determined in 20 mM Na-phosphate buffer (pH 6.5) containing 6 M guanidine hydrochloride using extinction coefficients at 280 nm computed for the individual mutants from their amino acid composition (31) utilizing the ExPASY proteomic WWW server software from the Swiss Institute of Bioinformatics (32).…”
Section: Methodsmentioning
confidence: 99%
“…of RetGC-In our previous study we found that disabling all three metal-binding EF-hands in GCAP-1 by mutations that nonselectively hampered both Ca 2ϩ and Mg 2ϩ binding failed to produce a constitutive, Ca 2ϩ -insensitive activation of RetGC-1 (22). That was contrary to what one would expect if the apo form of the GCAP were the activator form and argued that the substitution of Ca 2ϩ by Mg 2ϩ , rather than merely loss of Ca 2ϩ , was required to make GCAP-1 undergo the inhibitor-to-activator transition in the light.…”
Section: Mutations That Inhibit Cation Binding In Ef-hands Of Gcap-1 mentioning
confidence: 99%
See 3 more Smart Citations